Fostering EFL learners´ literacies through local inquiry in a multimodal experience - Rincón, July; Clavijo-Olarte, Amparo (Colombian Applied Linguistics Journal, 2016)
Addressing students’ social reality through the exploration of community inquiries in the English language class can create learning environments for developing students’ language and literacies. This paper addresses the ways in which community inquiries create opportunities for students to explore social and cultural issues in their neighborhoods using multimodality. It discusses the role community inquiries play in the development of literacy practices of a group of 10th graders in their EFL class. This descriptive qualitative project carried out at a public institution in the south of Bogotá, Colombia involved 40 participants. The goal of the project was to transform the way students relate to the community in order to create local knowledge. Data was collected through videotape recordings of students’ presentations, teacher’s journal, students’ interactions on Facebook, and students’ blogs over a two-year period. The findings reveal that teachers and students enacted a critical pedagogy through an inquiry curriculum that explored community issues and allowed participants to become inquirers of their own realities. Students’ language learning was evident in multimodal texts in English in their blogs, in the use of EFL in their oral presentations, and in their comments in response to peers on Facebook and their blogs.